2013
DOI: 10.12948/issn14531305/17.2.2013.01
|View full text |Cite
|
Sign up to set email alerts
|

Does ICT Participate in Economic Convergence among Asian Countries: Evidence from Dynamic Panel Data Model

Abstract: Conventional Convergence models usually oversee the role of information and communications technology (ICT) as a determinant of convergence. This paper introduces ICT as a fac- Keywords: Convergence Models, Information and Communication Technology (ICT), System Generalized Method of Moments (SYS-GMM), Human Development Index (HDI), Electricity Consumption IntroductionImportance of information has been pivotal since beginning of human civilization. Since time immemorial the information has been serving as a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…or GDP per capita in purchasing power parity (PPP) terms (Balaban, 2012;Mehmood & Azim, 2013) to represent a country's economic level and explore the relationships with ICT development. Studies also use high numbers of telephone lines per 100 inhabitants to represent industrialization (Hudson, 1995;Hudson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…or GDP per capita in purchasing power parity (PPP) terms (Balaban, 2012;Mehmood & Azim, 2013) to represent a country's economic level and explore the relationships with ICT development. Studies also use high numbers of telephone lines per 100 inhabitants to represent industrialization (Hudson, 1995;Hudson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The internet has quietly and successfully penetrated all aspects of life. Numerous studies have consistently shown its significant impact on the real economy, industrial manufacturing, financial development, technological innovation, transportation, and other fields (7,8), as well as its contribution to significant changes in residents' health, economic decision-making, payment methods, leisure and entertainment, and social interactions (9,10). Although scholars have conducted research on the relationship between the internet and the health of residents, gaps remain.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…They claimed that social protection spending would increase income inequality, and government expenditure on housing would also have an adverse impact on the distribution of income. Mehmood and Azim () demonstrated that information and communication technology played an important role in economic convergence among Asian countries. Li and Yu () studied whether financial reform could reduce income inequality in Asia.…”
Section: Literature Reviewmentioning
confidence: 99%